(untitled) (Journal of Science and Technology, 2024)
Radiation therapy accuracy and consistency are crucial in cancer treatment. However, technical issues such as machine breakdowns, can compromise radiation delivery, leading to non-uniform dose distribution, hot or cold spots, and, suboptimal treatment outcomes including local tumor recurrence. This study assesses the photon beam parameters of the Varian Clinac iX Linear Accelerator at Komfo Anokye Teaching Hospital to ensure the machine’s clinical reliability. Beam profiles were analyzed for 6 MV and 16 MV photon energies, using a 30 x 30 x 30 cm3 water phantom, electrometer, and ionization chamber. Measurements were taken at different depths for 10 × 10 cm2 and 15 × 15 cm2 field sizes. The beam flatness and symmetry of the 6 MV photon energy ranged from 0.88 % to 2.22 % and 0.25 % to 0.78 %, respectively, for the 10 × 10 cm2 field size, and from 1.39 % to 2.34 % and 0.57 % to 0.96 %, respectively, for the 15 × 15 cm2 field size. Flatness and symmetry for the 16 MV photon energy ranged from 1.98 % to 2.42 % and 0.36% to 1.04 % for the 10 × 10 cm2 field size, and from 1.25 % to 2.55 % and 0.25 % to 0.67 % for the 15 × 15 cm2 field size. The measured charge for 6 MV photon was 16.59 nC while the 16 MV photon energy measured 19.28 nC. The findings indicate that the Linear Accelerator is in good condition for clinical use. However, regular quality control checks are recommended to maintain its performance and ensure the consistent and accurate cancer treatment.